Differences in Risk Factors between Simple Febrile Seizures and Complex Febrile Seizures - Annisa Muhyi; Muhammad Harbiyan Acikdin; Iskandar Muda (Fakultas Kedokteran, 2023)
Introduction: Febrile seizures are seizures caused by an increase in body temperature above 38oC and not due to an intracranial infection. The incidence of febrile seizures is frequently reported in boys and 2-5% occur at the age of 6-60 months. Simple febrile seizures (SFS) are generalized tonic and/or clonic seizures without focal movement lasting less than 15 minutes and can stop on their own. Complex febrile seizures (CFS) are characterized by focal or focal seizures becoming generalized, recurring within 24 hours and lasting more than 15 minutes. Several risk factors can cause seizures in children such as the child's age, gender, comorbidities, body temperature, family history of seizures, nutritional status, leukocyte count and hemoglobin level. Methods: Analytical observational study with analysis test using Mann-Whitney U to see the difference of two independent samples between simple febrile seizures and complex febrile seizures. Samples were taken by purposive sampling with inclusion and exclusion criteria. Results: In this study, the results showed that there was no difference in risk factors between simple febrile seizures and complex febrile seizures with a p-value > 0.05. In this study, the results showed that there was no difference in risk factors between simple febrile seizures and complex febrile seizures with a p-value > 0.05. Conclusion: There is no difference in risk factors between simple febrile seizures and complex febrile seizures, but there are risk factors that have a synergistic effect on the occurrence of seizures in children aged 0-60 months.